Zakaj je Aleksander Veliki praznih rok? - Svetina, Ivo (Jezik in slovstvo, 2015)
The article analyses two essays by Taras Kermauner in which he discusses two Slovenian plays about the historical figure Alexander the Great: Alexander the Empty Handed (Aleksander praznih rok) by Vitomil Zupan and Alexander the Great (Aleksander Veliki) by Vladimir Kavčič. Particular emphasis is placed on the sections in which Kermauner addresses the topics of the revolution whose ideals are never fulfilled and the despot/dictator who, under the pretext of changing the world, sets out on a campaign of conquer and is sooner or later forced to eliminate his most faithful companions in arms.
Keywords: Zupan, Vitomil, 1914-1987; "Aleksander praznih rok"; Kavčič, Vladimir, 1932-2014; "Aleksander Veliki"; Slovene literature; slovenska književnost; slovenski dramatiki; slovenska dramatika; slovenska povojna dramatika; diktatorji; revolucije; nasilno spreminjanje sveta; demitizacija; nihilizem